A Capitol Orchard: Botanical Networks and the Creation of a Japanese 'Neo-Europe'. Issue 2 (19th September 2022) - Thornton, Michael
Abstract: In the second half of the nineteenth century, the ethnic Japanese ( wajin ) population of Hokkaido ballooned from roughly sixty thousand residents, primarily living on the island's southern tip, to more than two million people, scattered across the island. This explosive colonization was part of a global wave of settler colonialism. The wajin colonial regime and the foreign advisers they hired helped turn indigenous Ainu territory into Japan's first modern colony and one of its most important agricultural breadbaskets, resembling the so-called Neo-Europes of the Anglophone settler world. Hokkaido's history fits into the framework of ecological imperialism developed by Alfred Crosby and expanded by many scholars since. But the role of city building in processes of ecological imperialism remains understudied. Scholars who do discuss urbanization in the context of ecological imperialism focus on cities' roles as markets, downplaying their importance as sites of state power and political interventions. In Hokkaido, however, the politics and policies of city building were crucial tools of Japanese ecological imperialism. Colonial authorities built Hokkaido's capital, Sapporo, as a colonial laboratory, importing ideas from Japan and abroad, recording their experiences in Hokkaido, and ultimately exporting that knowledge to Japan's later colonies in East Asia.